Peran Guru Pendidikan Agama Kristen dalam Meningkatkan Motivasi siswa Belajar Mandiri di masa Pandemi Covid-19 - Rahul Zefanya; Reni Trifosa (STAK Reformed Remnant Internasional, 2022)
This achievement and success in the learning process during the COVID-19 pandemic is certainly the hope of all education activists and the hope of Christian Religious Education Teachers because a teacher becomes an influential person in the growth and development of student learning. Christian Religious Education Teachers are examples and role models for every student, therefore Christian Religious Education Teachers have responsibilities and duties as motivators for their students. The purpose of this study was to describe the role of a Christian Religious Education teacher in increasing student motivation to learn independently during the Covid-19 pandemic. This study uses a literature method with a descriptive qualitative approach. As a result, it was concluded that Christian Religious Education Teachers are expected to be able to develop the potential that exists in students even though during the Covid-19 pandemic, a Christian Religious Education Teacher is also not only required to be skilled and disciplined in learning, but Christian Religious Education Teachers can also be a motivator for students. the students. Christian Religious Education teachers play a role in teaching good traits and character so as to produce students who have good character and can become facilitators who meet the needs of students.